An everyday clinical challenge in the COVID 19 pandemic era – how to treat patients with pulmonary embolism and hemoptysis: COVID 19 and pulmonary embolism - Stojanovic, Duska; Stojanović, Milovan M; Marjanovic, Dusan; Mitrovic, Goran; Stalevic, Marko; Stojanovic, Vidosava (Halo 194 Scientific Journal of Emergency Medicine, 2022)
Introduction. Pulmonary embolism (PE) is a relatively common complication in COVID 19. The cornerstone of PE medical treatment is anticoagulant therapy. However, anticoagulants may cause severe bleeding. Patients with PE and hemoptysis are often very difficult to treat. Case report. We presented a case of a young patient who developed a COVID 19 induced pneumonia. During hospital treatment, he developed PE why the dose of anticoagulants was increased. Soon after the dose was increased, the patient developed massive hemoptysis. A team of physicians decided to continue with anticoagulants and to introduce a hemostatic into the therapy. The patient responded well to the therapy and he was dismissed from the hospital after two weeks of treatment. Conclusion. Patients with PE and hemoptysis are often difficult to treat as the treatment of PE can worsen hemoptysis. This is why the decision on the treatment should be made by a team of physicians.